EVALUASI PERHITUNGAN DAN PENYETORAN PAJAK PENGHASILAN PASAL 22 ATAS PENGADAAN BARANG PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA (KPPN) KOTAMOBAGU - Baharta, Zulkarnain; Elim, Inggriani; Wokas, Heince R.N (Universitas Sam Ratulangi, 2020)
The Indonesian government requires a significant amount of funds for the national development process both at the central and regional levels. For welfare and prosperity, it can help, one of the efforts to realize national development as the case with domestic resources consisting of taxes. One of the taxes set by the government is the tax that is imposed on the tax that is said to be received in the tax year or can also be taxed on translation in part of the tax year. The taxation included in Article 22 of Income Tax is also not part of fiscal policy, because it is a type of tax requested by the government. Article 22 of the procurement tax on the procurement of goods in the municipal treasury office in Kotamobagu is in accordance with the prevailing laws and regulations, taxation regulations and transfers. Descriptive qualitative method used in this study with data collection techniques consisting of interviews, documentation and observation. Data that has been collected from informants is then completed with the stages of data reduction, data presentation and conclusion completion. The results of the study found that KPPN at Kotamobagu City in the PPh article 22 was appropriate and some was not in accordance with Law No. 36 of 2008 concerning tax translation and Regulation of the Minister of Finance No. 34/PMK.010/2017 concerning tax collection Learn article 22 regarding payment or delivery of goods and activities in important fields or business activities in other fields. KPPN is not consistent with Minister of Finance Regulation No. 34/PMK.010/2017 concerning tax collection which addresses article 22.